Anaerobic baffled reactor (ABR): pengelolaan air limbah komunal pada pesantren Salafiyah Syafi’iyah di Situbondo - Rifaini, Intan; Noerhayati, Eko (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Water is a crucial element for life, both for internal body processes and daily activities. However, the nature of water as a primary resource makes its use less appropriate. This condition has an impact on the decline in water quality in several aspects. This happened at the Salafiyah Syafi'iyah Islamic Boarding School in Sukorejo, Situbondo. This boarding school experienced an increase in students and resulted in an increase in black water and gray water domestic waste. Methods: Researchers are trying to find solutions based on research with the Anaerobic Baffled Reactor (ABR) method. This research aims to produce waste water sanitation. Sanitary planning research uses two data sources, namely primary and secondary. Findings: The result of this research is knowing the existence of two types of waste discharge, namely domestic waste and non-domestic waste at the boarding school. Conclusion: Another result, namely the use of ABR-based treatment plants has advantages. This advantage focuses on the aspect of land area, construction, operation, maintenance and cost efficient wastewater treatment plants. Furthermore, researchers have found an ABR water treatment plant design model with the dimensions of each compartment in the form of length x width x height.